Unpacking the Pay Satisfaction Paradox: The Interplay of Work Pressure and Life Balance in Predicting Employee Turnover within Urban Hospitality - Sophia Widya Kirana; Budi Prabowo (Jurnal Investasi Islam, 2026)
High employee turnover (12% in 2023) at Fave Hotel Rungkut Surabaya necessitates a rigorous investigation into retention determinants. This study analyzes the influence of work pressure, pay satisfaction, and work life balance on turnover intention through the lens of Social Exchange Theory. Employing a quantitative explanatory research approach, data were collected from a census of 50 employees using a 4-point forced choice Likert scale. Multiple linear regression analysis reveals that these factors simultaneously explain 66.7% of the variance in turnover intention ( = 0.667). Partially, work pressure emerged as the most dominant positive driver of exit intentions. Notably, the study identifies a "mobility anomaly" where pay satisfaction exerts a significant positive influence (  = 3.002,  = 0.004), suggesting that financial contentment validates employees' perceived market value and catalyzes career migration. Conversely, work life balance acts as a crucial protective anchor with a significant negative effect. These findings challenge traditional assumptions by demonstrating that in competitive hospitality markets, pay satisfaction can drive professional withdrawal. Management is advised to prioritize restorative psychological contracts through life balance initiatives and systematic workload management to mitigate turnover effectively.